A 20-Year Analysis of Economic & Renewable Energy Policies Across Wisconsin: A Multi-Scale Analysis of Institutional Player Disjuncts - Kazimierczuk, Kamila; Miller, Laura J. (My University, 2019)
While Wisconsin has produced relatively fewer greenhouse gas (GHG) emissions than some of its Midwestern neighbors, in 2003 it was the 42nd largest GHG emitter in the world. The state of Wisconsin generates only 10-percent of its net electricity from renewable energy. It has continued to lag behind the rest of the country as many other states have made considerable progress. Within Wisconsin there are two smaller-scaled regions that have made varying amounts of progress with renewable energy use. The city of Madison currently gets 49-percent of its electricity from renewable energy and the University of Wisconsin-Madison obtains just 15-percent of its annual electricity from renewables. Though this is the case, their paths to reach this point and the methods through which they are doing so vary greatly based on policy, economic feasibility, and contractual relationships to utility providers. The shift to renewables is vital to preventing further environmental degradation, which has been a recurring trend as global climate change threatens to produce devastating impacts all around the world. Our research seeks to answer these questions: 1. How have the institutional linkages between the state, capital, and university governed the development and deployment of renewable energy over the past two decades? 2. How have these linkages co-evolved over time, with respect to the state’s Renewable Portfolio Standard targets? 3. How have institutional player disjuncts between the City of Madison, UW-Madison and public utility company Madison Gas & Electric affected renewable energy implementation? The disjuncts between the renewable energy policies, investments, and histories of each level of government—the state, the city, and the campus—make it exceedingly difficult for meaningful synergies and collective goal-setting to be made on any scale. As a result, we intend to analyze official documents, initiatives, legislation, and reports made by the governing bodies on each level to analyze the interconnections, or lack thereof, between all three. In doing so, we hope to better understand the political and economic forces guiding the implementation and deployment of renewable energy sources across Wisconsin. By evaluating the linkages between these institutional players, we can identify inefficiencies between them and better understand how to incorporate synergies, or increased collaboration and coordination amongst these different authorities, going forward.
Includes Figures, Charts, Tables, Maps and Bibliography.
Keywords: Madison; State of Wisconsin; University of Wisconsin - Madison; Renewable energy; Madison Gas and Electric